A whirlpool of emotion: How entrepreneurs’ empathy affects employees‘ emotional exhaustion - Xu, Jiang; Dong, Baobao; Wang, Yinong; Jiang, Na; Gao, Yue (Frontiers in Psychology, 2022)
Drawing upon upper echelons and self-determination theories, we hypothesize and test a mediating process linking entrepreneurs' empathy to employees` emotional exhaustion and the moderating role of psychological empowerment. Based on a dyadic-survey study of entrepreneurs and their employees in high-tech new ventures in China, we conduct the empirical test by using hierarchical linear modeling and find that entrepreneurs' empathy has a negative effect on employees` emotional exhaustion, psychological empowerment not only partially mediates the relationship between entrepreneurs' empathy and employees` emotional exhaustion, but also positively moderates the above relationship. This study frames an integrative perspectives of emotions and psychologies and sheds nuanced understanding on the mechanisms linking empathy with emotional exhaustion. Limitations and future directions are addressed.